KURIKULUM PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN - Syafana, Putri Tsilvya; Khusna, Atina; Maulana, Muhammad Irfan; Huda, Ahmad Alamul (JURNAL KAJIAN ISLAM MODERN, 2024)
In the context of education, success does not only depend on one component, but involves all components that are interrelated with each other, so that the main objectives of education can be achieved. Planning, which is the foundation of every scientific activity, must be carried out in a structured and systematic manner. Similarly, education requires planned programs that can guide the education process towards the desired goals. The educational process, from implementation to assessment, is known as the curriculum. Curriculum is an important component in education as it carries out the desired goals; in fact, without the involvement of curriculum, the goals will not be achieved. The curriculum, as one of the core components of education, has a structure consisting of various complementary components, including objectives, structure, programs, implementation strategies, assessment of learning outcomes, guidance-counselling, and educational administration and supervision.